THE INFLUENCE OF MORALE AND COMPENSATION ON ORGANIZATIONAL PERFORMANCE AT THE EDUCATION OFFICE TULANG BAWANG DISTRICT - Firdaus, Firdaus; Mustakim, Senen (Saburai International Journal of Social Sciences and Development, 2023)
This study aims to determine the effect of work enthusiasm and compensation on organizational performance at the Tulang Bawang Regency Education Office. The method used in this research is quantitative, using multiple linear regression analysis techniques. The sample in this study amounted to 26 employees. Data collection techniques include observation, documentation and questionnaire activities. The data analysis method uses a quantitative approach with the help of SPSS version 21.0 statistical tools including the calculation of validity tests, reliability tests, simple and multiple linear regression tests, t tests, F tests and coefficient of determination tests. The results of hypothesis testing show that the work enthusiasm variable partially has a positive effect on performance with a contribution of 46.4%. Compensation has a positive effect on performance with a contribution of 45.6%. Simultaneous hypothesis testing shows that the work enthusiasm and compensation variables together have a positive effect on the organizational performance variable with a contribution of 56.0%, while the remaining 44.0% is a variation of other variables outside this study. Keywords: morale, compensation, organizational performance